Ocrelizumab Treatment Modulates B-Cell Regulating Factors in Multiple Sclerosis. Issue 2 (26th March 2023) - Ho, Samantha; Oswald, Eva; Wong, Hoi Kiu; Vural, Atay; Yilmaz, Vuslat; Tüzün, Erdem; Türkoğlu, Recai; Straub, Tobias; Meinl, Ingrid; Thaler, Franziska; Kümpfel, Tania; Meinl, Edgar; et al.
Abstract : Background and Objectives: Antibodies to CD20 efficiently reduce new relapses in multiple sclerosis (MS), and ocrelizumab has been shown to be effective also in primary progressive MS. Although anti-CD20 treatments efficiently deplete B cells in blood, some B cells and CD20 − plasma cells persist in lymphatic organs and the inflamed CNS; their survival is regulated by the B cell–activating factor (BAFF)/A proliferation-inducing ligand (APRIL) system. The administration of a soluble receptor for BAFF and APRIL, atacicept, unexpectedly worsened MS. Here, we explored the long-term effects of ocrelizumab on immune cell subsets as well as on cytokines and endogenous soluble receptors comprising the BAFF-APRIL system. Methods: We analyzed immune cell subsets and B cell–regulating factors longitudinally for up to 2.5 years in patients with MS treated with ocrelizumab. In a second cohort, we determined B-cell regulatory factors in the CSF before and after ocrelizumab. We quantified the cytokines BAFF and APRIL along with their endogenous soluble receptors soluble B-cell maturation antigen (sBCMA) and soluble transmembrane activator and calcium-modulator and cyclophilin ligand (CAML) interactor (sTACI) using enzyme-linked immunosorbent assays (ELISAs). In addition, we established an in-house ELISA to measure sTACI-BAFF complexes. Results: Ocrelizumab treatment of people with MS persistently depleted B cells and CD20 + T cells. This treatment enhanced BAFF and reduced the free endogenous soluble receptor and decoy sTACI in both serum and CSF. Levels of sTACI negatively correlated with BAFF levels. Reduction of sTACI was associated with formation of sTACI-BAFF complexes. Discussion: We describe a novel effect of anti-CD20 therapy on the BAFF-APRIL system, namely reduction of sTACI. Because sTACI is a decoy for APRIL, its reduction may enhance local APRIL activity, thereby promoting regulatory IgA + plasma cells and astrocytic interleukin (IL)-10 production. Thus, reducing sTACI might contribute to the beneficial effect of anti-CD20 as exogenous sTACI (atacicept) worsened MS. Classification of Evidence: This study provides Class IV evidence that endogenous sTACI in blood and CSF is decreased after ocrelizumab treatment.